A chemically defined carrier for the delivery of human mesenchymal stem/stromal cells to skin wounds. - Walker, N; Mistry, A; Smith, L; Eves, P; Tsaknakis, G; Forster, S; Watt, S; Macneil, S (2012)
Skin has a remarkable capacity for regeneration, but age- and diabetes-related vascular problems lead to chronic non-healing wounds for many thousands of U.K. patients. There is a need for new therapeutic approaches to treat these resistant wounds. Donor mesenchymal stem/stromal cells (MSCs) have been shown to assist cutaneous wound healing by accelerating re-epithelialization. The aim of this work was to devise a low risk and convenient delivery method for transferring these cells to wound beds. Plasma polymerization was used to functionalize the surface of medical-grade silicone with acrylic acid. Cells attached well to these carriers, and culture for up to 3 days on the carriers did not significantly affect their phenotype or ability to support vascular tubule formation. These carriers were then used to transfer MSCs onto human dermis. Cell transfer was confirmed using an MTT assay to assess viable cell numbers and enhanced green fluorescent protein-labeled MSCs to demonstrate that the cells post-transfer attached to the dermis. We conclude that this synthetic carrier membrane is a promising approach for delivery of therapeutic MSCs and opens the way for future studies to evaluate its impact on repairing difficult skin wounds.